(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Background: Visfatin is a novel adipocytokine predominantly secreted from visceral fat and its blood shows insulin-mimetic effects which correlate with overweight, type 2 diabetes mellitus (T2DM) and inflammation. Overweight is an important component of metabolic syndrome. However, the relationship between visfatin levels and overweight is not yet clear. The aim of this study was to investigate the relationship of serum visfatin levels in overweight and apparently healthy subjects. Methodology: This was a cross-sectional comparative study includes 50 overweight subjects who had no disease conditions and 42 controls. Anthropometric measurements included Height (HT), body mass index (BMI), waist circumferences (WC) and hip circumferences (HC) were performed by using standard methods. Serum visfatin levels were analyzed by Enzyme Linked Immunosorbent Assay (ELISA). Biochemical parameters estimated by ELISA and standard methods where fasting serum visfatin, fasting serum insulin and fasting plasma glucose, serum triglycerideg (TG), serum cholesterol (CHOL) levels and lipid profiles were evaluated. All data were presented as Mean (M) and Standard Deviation (±SD) and results were compared with students t-test and correlation coefficient. The values were considered significant at 0.05 level of significance. Results: BMI, WC, HC and %BFM were significantly higher in overweight subjects compaired to controls. Serum visfatin (ng/ml) value in overweight subjects also was observed significantly higher compared to the controls. Conclusion: A significant corelation of plasma visfatin levels was observed with anthropometric parameters whereas no significant relationship observed with any of the biochemical parametres either the study subjects or controls. This study shows correlation between serum visfatin and overweight subjects. Future studies with large population possibly will explore and explain the role and relationship of serum visfatin with overweight, T2DM and others diseases as related to visfatin. Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 91-95